John Locke on toleration, (in)civility, and the quest for concord - Bejan, T (Imprint Academic, 2016)
Lockean toleration has long been criticized as ethically minimal and indifferent to the interactions of private individuals. Yet these criticisms ignore Locke’s lasting preoccupation with intolerance and incivility as obstacles to coexistence. These concerns were instrumental in the development of his understanding of toleration as a complex package of negative and positive virtues informed increasingly by a vision of concordia — a Christian ideal of unity in diversity. But by linking the outward virtue of civility ever more closely with sincere esteem and inward charity, Locke ultimately premised affective concord on an agreement between individuals more “fundamental” than the disagreements that divided them. Re-interpreting Lockean toleration — and its limits — in this light has important implications for both its critics and defenders who likewise prefer concord to mere toleration while neglecting its exclusionary potential.